THE FLAVOR OF NAMES: HOW YOGYAKARTA CAFÉS BRAND THEIR BEVERAGES - Fitria Amanda; Ajar Pradika Ananta Tur (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2026)
This research investigates the impact of beverage names on consumers' perceptions and decisions. For instance, names like